Respuesta :
[tex]4x^2+4x=0 \\
4x(x+1)=0 \\
4x=0 \ \lor \ x+1=0 \\
x=0 \ \lor \ x=-1 \\
\hbox{two solutions} \\ \\
x^2+6x+9=0 \\
(x+3)^2=0 \\
x+3=0 \\
x=-3 \\
\hbox{one solution}[/tex]
[tex]9x^2-25=0 \\ (3x)^2-5^2=0 \\ (3x-5)(3x+5)=0 \\ 3x-5=0 \ \lor \ 3x+5=0 \\ 3x=5 \ \lor \ 3x=-5 \\ x=\frac{5}{3} \ \lor \ x=-\frac{5}{3} \\ \hbox{two solutions} \\ \\ 5x^2+20x+20=0 \\ x^2+4x+4=0 \\ (x+2)^2=0 \\ x+2=0 \\ x=-2 \\ \hbox{one solution}[/tex]
[tex]x^2-x-6=0 \\ x^2+2x-3x-6=0 \\ x(x+2)-3(x+2)=0 \\ (x-3)(x+2)=0 \\ x-3=0 \ \lor \ x+2=0 \\ x=3 \ \lor \ x=-2 \\ \hbox{two solutions}[/tex]
The equations which have only one solution are: x²+6x+9=0 and 5x²+20x+20=0,
[tex]9x^2-25=0 \\ (3x)^2-5^2=0 \\ (3x-5)(3x+5)=0 \\ 3x-5=0 \ \lor \ 3x+5=0 \\ 3x=5 \ \lor \ 3x=-5 \\ x=\frac{5}{3} \ \lor \ x=-\frac{5}{3} \\ \hbox{two solutions} \\ \\ 5x^2+20x+20=0 \\ x^2+4x+4=0 \\ (x+2)^2=0 \\ x+2=0 \\ x=-2 \\ \hbox{one solution}[/tex]
[tex]x^2-x-6=0 \\ x^2+2x-3x-6=0 \\ x(x+2)-3(x+2)=0 \\ (x-3)(x+2)=0 \\ x-3=0 \ \lor \ x+2=0 \\ x=3 \ \lor \ x=-2 \\ \hbox{two solutions}[/tex]
The equations which have only one solution are: x²+6x+9=0 and 5x²+20x+20=0,
Answer:
The equations which have only one solution are x²+6x+9=0 and 5x²+20x+20=0,
Step-by-step explanation: